Comparative differences in the risk of major gastrointestinal bleeding among different direct oral anticoagulants: An updated traditional and Bayesian network meta-analysis - Chen, Xiuehui; Wang, Lili; Li, Huijun; Huang, Weichao; Zhao, Lingyue; Guo, Wenqin (Frontiers in Pharmacology, 2023)
Background: The most favorable gastrointestinal (GI) bleeding safety profile among different types of NOACs remains controversial. This meta-analysis that included the latest studies aimed to compare GI bleeding risk associated with the use of various NOACs. Methods: PubMed, Cochrane library, and clinicaltrial.gov were searched. Randomized control trials (RCTs) evaluating the safety of NOACs were identified. The primary endpoint assessed was major GI bleeding. Results: A total of 37 RCTs were included in the analyses. Base on traditional meta-analysis, the major GI bleeding risk was different among various NOACs (interactive P value < 0.10). Network meta-analysis findings showed that no NOACs increased risk of major GI bleeding compared with the conventional therapy. Furthermore, 10 mg daily apixaban reduced major GI bleeding risk more than daily 60 mg edoxaban, ≥ 15 mg rivaroxaban, and 300 mg dabigatran etexilate, while no difference was observed between daily 300 mg dabigatran etexilate, 60 mg edoxaban, and ≥ 15 mg rivaroxaban. Major GI bleeding risk associated with 30 mg daily edoxaban was lower than that of 10 mg daily rivaroxaban, and no differences between daily 5 mg apixaban, 30 mg edoxaban, and 220 mg dabigatran etexilate were observed. Major GI bleeding risk differences were observed when various NOACs were compared. Conclusion: Among standard-dose NOACs, apixaban use was associated with the lowest degree of major GI risk. Among low-dose of NOACs, edoxaban was associated with a lower major GI bleeding risk than rivaroxaban.